Agar‐Derived Nitrogen‐Doped Porous Carbon for CO2 Adsorption. Issue 39 (22nd October 2018) - Xu, Jianguo; Cui, Hongmin; Shi, Jinsong; Yan, Nanfu; Liu, Yuewei; Li, Dan
Abstract: An efficient carbonaceous CO2 adsorbent with doped nitrogen element is derived from agar. Agar was mixed with urea and the mixture was then carbonized. After chemical activation with KOH, nitrogen doped microporous carbon was obtained. The nitrogen content was up to 8.58 wt %, depending on the preparation conditions. The CO2 adsorption properties, including the adsorption isotherms, the isosteric heat of adsorption and the adsorption selectivity were studied. The highest CO2 uptake of 6.5 mmol g −1 (273 K, 1 bar) was achieved by a carbon activated at 600 °C with moderate nitrogen content, while the carbon activated at 550 °C exhibited the best CO2 /N2 selectivity of 37. The current work exploits the potential use of agar as carbon precursor for CO2 adsorbent, and provides a convenient and effective approach to nitrogen doping. Abstract : A very convenient strategy for the preparation of nitrogen containing carbon from biomass was developed in this work. Nitrogen doped carbons were prepared from the mixture of agar and urea. The carbons exhibited high porosity and great potential for the application in CO2 adsorption. A high CO2 uptake of 6.5 mmol g −1 was achieved at 273 K and 1 bar.